The Relationship Between Spiritual Quality and Self-Adaptation in Cancer Patients Receiving Chemotherapy: Spiritual Quality and Self-Adaptation in Cancer Patients - Nursalam, Nursalam; Triharini , Mira; Azza, Awatiful; Chanif, Chanif; Wahyuni, Erna Dwi; Machmudah, Machmudah; Safaah, Nurus; Utami, Sri; Kusumaningrum, Tiyas; Nurbadriyah, Wiwit Dwi; Satriya (Scripta Medica, 2023)
Background/Aim: Previous research obtained information that chemotherapy patients need more spirituality than patients with other diseases because chemotherapy patients feel that their illness is difficult to heal and will last forever, until the end of their lives. The purpose of this study was to find a relationship between spiritual qualities and the self-acceptance of cancer patients receiving chemotherapy. Methods: The study sample was 125 patients in chemotherapy. The investigative method used a correlation with a cross-sectional approach. The spiritual quality questionnaire was based on the spiritual well-being scale measurement technique which contained 3 components, namely spirituality and faith, emotional support and meaning in life. The instrument consisted of 20 multiple-choice questions with 6 Likert measurement scales. Data analysis used univariate and bivariate analysis. The significance level was set at p < 0.05. Results: The results of the investigation showed that there was a significant positive relationship between spiritual quality and self-adaptation of respondents who were cancer patients who received chemotherapy in the Flamboyan Room of Balaidhika Husada Hospital Jember, Indonesia as evidenced by a significant p < 0.01. Conclusion: This study showed positive correlation between spiritual quality and self-adaptation of cancer patients receiving chemotherapy. The results of this study can assist nurses in providing chemotherapy patient care through a spiritual approach.